2019
DOI: 10.1021/acsami.9b03089
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Convective Segregation of Different Sized Microparticles

Abstract: Using computational modeling, we design a facile method for sorting particles of different sizes in a fluid-filled microchamber. The microchamber is inclined at an angle with respect to the horizontal direction and contains suspended gold nanoparticles as well as the microparticles. With the application of ultraviolet light, the heat generated by illuminating the gold nanoparticles gives rise to thermal buoyancy effects, which drive the flow of the fluid in the chamber. This thermally driven, convective flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Manna et al. predicted that on an incline plane, because of the competing effects of gravity and convective fluid flow, particles of different sizes will settle out at heights where the two effects cancel out [25] . Our experiments bear this out and the setup is shown in Figure 7.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Manna et al. predicted that on an incline plane, because of the competing effects of gravity and convective fluid flow, particles of different sizes will settle out at heights where the two effects cancel out [25] . Our experiments bear this out and the setup is shown in Figure 7.…”
Section: Resultssupporting
confidence: 55%
“…Larger particles will sometimes become trapped in a bed of smaller particles, which can be alleviated by moving the irradiation point uphill incrementally. It is also of note that the flow center becomes slightly shifted downhill away from the irradiation point due to the effect of gravity [25] . Upon turning off the light, all the particles move to the bottom of the cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sen and Balazs showed that in the presence of light, freely suspended TiO 2 nanoparticles generate photothermal flow fields that pump inert microparticles towards the light, with flow rates tightly controlled by nanoparticle concentration and light intensity [46]. Using these directed flows, they further demonstrated the reversible construction and transport of colloidal crystals (Figure 3C), as well as facile methods for sorting microparticles of different sizes and densities [50]. In another report, the convective flows induced by illuminating a selected area with near infrared (NIR) light was demonstrated (Figure 3D) [51].…”
Section: Micropumpsmentioning
confidence: 95%
“…To address real-world needs for manipulation and fabrication of micro/nanomaterials, a number of micro-/nano-scaled methods have been presented. Typical examples include microfluidic [14,15], acoustic [16,17], electrokinetics [18,19], magnetic [20,21], optical [22,23], thermal [24,25], and atomic force microscope [26,27] approaches. An emerging topic on the manipulation and fabrication of micro/nanoparticles is about how to develop a novel mechanism that can complement what a single technique can offer.…”
Section: Introductionmentioning
confidence: 99%